Corrosion tests and standards : application and interpretation - Baboian, Robert, 1934-2015 (West Conshohocken (Pa.) : ASTM, 2005)
Addresses the worldwide problem of corrosion of metals and alloys, and provides guidelines for recognizing types of corrosion, as well as the fundamentals of corrosion testing. The technical quality and value of this manual is the result of the efforts of over 400 experts in the field of corrosion testing and evaluation. Their work provides a complete coverage of application and interpretation of corrosion tests and standards. In eight sections: General Information Testing and Evaluation Types of Tests Testing for Corrosion Types Testing in Environments Materials Testing Testing in Industries Corrosion Referencing.
Keywords: Corrosie; Corrosiebestrijding; Meettechnieken